Method for manufacturing MCMB
The MCMB manufacturing method addresses high-cost issues by using isotropic pitch with water-soluble salts to achieve anisotropic properties at lower temperatures, enhancing productivity and reducing costs.
Patent Information
- Application Number
- JP2024543438
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-19
- Filing Date
- 2022-01-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-01-21
AI Technical Summary
Existing MCMB manufacturing methods using isotropic pitch require high temperatures and long reaction times, leading to increased costs and decreased yield due to the need for conversion to anisotropic pitch and the inclusion of thermosetting resin.
A method involving pretreatment of isotropic pitch, mixing with water-soluble metal chloride salts, grinding and stirring, heating at 150 to 300°C for 30 to 180 minutes, and removing salts to produce MCMB, utilizing isotropic pitch to achieve anisotropic properties at lower temperatures.
This method reduces energy input, shortens reaction time, and lowers production costs by inducing polymerization at lower temperatures, producing high-quality MCMB while using lower-cost raw materials.
Smart Images

Figure 2025502474000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing an MCMB, and more particularly to a method for manufacturing an MCMB that can reduce the manufacturing cost of the MCMB. [Background technology]
[0002] Generally, mesophase carbon microbeads (MCMB) are produced by heating pitch at high temperatures. Pitch exhibits optically isotropic properties, but when it is heat-treated at 380℃ or higher, a polymerization reaction occurs simultaneously with pyrolysis, producing mesophase carbon microbeads with optically anisotropic properties. When it is subsequently heat-treated, the particles of the mesophase carbon microbeads gradually grow, and above a certain temperature, the microbeads bond to each other and become coke. The mesophase carbon microbeads (MCMB) produced by this heat treatment process have a well-developed crystal structure due to the stacking of aromatic rings, and therefore have excellent electrical and mechanical properties. They are used as a negative electrode material for lithium secondary batteries and as a basic material in the manufacturing process of various high-strength, high-density carbon materials.
[0003] Korean Patent Publication No. 10-1999-0083663 (Manufacturing method of granular carbon material, published on December 6, 1999) describes a method in which pitch and polymer resin are mixed, reacted at 500 to 600°C, cooled, and the resulting material is pulverized and classified to obtain a powder.
[0004] However, in this method, the quality of the final product is greatly affected by the quality of the pitch itself, so if anisotropic pitch is used, or if isotropic pitch is used, it is necessary to convert it to anisotropic pitch, and the yield is reduced due to the inclusion of a thermosetting resin.
[0005] In addition, when converting isotropic pitch into anisotropic pitch, a heat treatment is performed at a high temperature of 500 to 600° C., which increases the manufacturing cost. Summary of the Invention [Problem to be solved by the invention]
[0006] In consideration of the above-mentioned conventional problems, the technical problem to be solved by the present invention is to provide a method for manufacturing MCMB that can reduce the energy input when manufacturing anisotropic pitch using isotropic pitch.
[0007] Another object of the present invention is to provide a method for producing MCMB, which can relatively lower the reaction temperature of pitch, shorten the time required for the reaction, improve productivity, and reduce production costs. [Means for solving the problem]
[0008] A method for producing MCMB according to a preferred embodiment of the present invention may include the steps of: a) pretreating a raw pitch; b) mixing the pretreated pitch with a salt; c) pulverizing and stirring the mixture of the pitch and salt; d) heating and stirring the pulverized mixture at a temperature of 150 to 300°C for 30 to 180 minutes to pyrolyze and polymerize the raw pitch to produce mesophase pitch; e) cooling the heated and stirred mixture and then removing the salt; and f) post-treating the mesophase pitch from which the salt has been removed to produce MCMB.
[0009] In an embodiment of the present invention, the raw pitch may be an isotropic pitch having a softening point of 150 or 115. In an embodiment of the present invention, step a) may include sieving the dried raw pitch to homogenize it to a particle size of 106 μm or less, and drying the homogenized raw pitch in an oven.
[0010] In an embodiment of the invention, the salt in step b) may be a water-soluble metal chloride. In an embodiment of the present invention, the metal chloride may be a mixture of aluminum chloride and sodium chloride in a molar ratio of 3:2 to 1:1.
[0011] In an embodiment of the present invention, the mixing ratio of the raw material pitch and the metal chloride may be 5 to 30 wt % raw material pitch and 70 to 95 wt % salt. In an embodiment of the present invention, in step e), water-soluble salts can be removed by washing with distilled water.
[0012] In an embodiment of the present invention, in step f), MCMB may be produced by drying the mesophase pitch in a vacuum atmosphere and then subjecting it to solvent extraction. Effect of the Invention
[0013] The method for producing MCMB according to the present invention has the effect of improving productivity and reducing production costs by producing MCMB by inducing a polymerization reaction using a molten salt at a temperature lower than 380°C, which is known for pitch.
[0014] In addition, the present invention is capable of producing anisotropic MCMBs using isotropic pitch, which has the effect of reducing the cost of raw materials and the cost of processing the raw materials. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a process flow chart of a method for manufacturing an MCMB according to a preferred embodiment of the present invention. [Diagram 2] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Diagram 3] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 4] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Diagram 5] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 6] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 7]2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 8] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 9] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 10] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 11] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. [Figure 12] 2 to 12 are Raman shift graphs showing the results of various experimental examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the method for producing an MCMB according to the present invention will be described in detail with reference to the accompanying drawings. The embodiments of the present invention are provided to more completely explain the present invention to those having ordinary skill in the art, and the following embodiments may be modified into various other forms, and the scope of the present invention is not limited to the following embodiments. Rather, these embodiments are provided to make the present disclosure more complete and complete, and to fully convey the idea of the present invention to those skilled in the art.
[0017] The terms used in this specification are used to describe specific embodiments and are not intended to limit the present invention. As used in this specification, the singular form includes the plural form unless the context clearly indicates otherwise. In addition, as used in this specification, "comprise" and / or "comprising" specify the presence of a stated shape, number, step, operation, member, element, and / or group thereof, but do not exclude the presence or addition of one or more other shapes, numbers, operations, members, elements, and / or groups thereof. As used in this specification, the term "and / or" includes any one and any combination of one or more of the listed items.
[0018] In this specification, terms such as first and second are used to describe various members, regions and / or parts, but these members, parts, regions, layers and / or parts should not be limited by these terms. These terms do not imply a specific order, up or down, or superiority or inferiority, but are used only to distinguish one member, region or part from another member, region or part. Therefore, a first member, region or part described below can refer to a second member, region or part without departing from the spirit of the present invention.
[0019] Hereinafter, embodiments of the present invention will be described with reference to the drawings which show schematic diagrams of embodiments of the present invention. In the drawings, for example, variations in the shapes shown are expected due to manufacturing techniques and / or tolerances. Therefore, embodiments of the present invention should not be limited to the specific shapes of regions shown in the present specification, but should include, for example, variations in shapes caused by manufacturing.
[0020] FIG. 1 is a process flow chart of a method for manufacturing an MCMB according to a preferred embodiment of the present invention. Referring to FIG. 1, the present invention includes a step of pretreating raw pitch (S10), a step of mixing the pretreated pitch with salt (S20), a step of pulverizing and stirring the mixture of pitch and salt (S30), a step of heating and stirring the pulverized mixture at a temperature of 150 to 300° C. for 30 to 180 minutes to pyrolyze and polymerize the pitch to produce mesophase pitch (S40), a step of cooling the heated and stirred mixture and removing the salt (S50), and a step of post-treating the mesophase pitch from which the salt has been removed to produce MCMB (S60).
[0021] The configuration and operation of the method for producing an MCMB according to the present invention configured as above will now be described in more detail. First, the raw pitch is pretreated as in step S10.
[0022] In this case, the pretreatment is to sieve the dried raw pitch to homogenize it to a particle size of 106 μm or less, and then dry the homogenized raw pitch in an oven. In this case, the drying conditions are to heat it to 40°C in a vacuum atmosphere to completely dry it. In this case, the raw pitch is an isotropic pitch.
[0023] In this case, the drying time can be adjusted according to the amount of raw material pitch. Next, the dried raw pitch is mixed with salts as in step S20. In this case, the salt may contain sodium chloride, and is preferably a mixture of sodium chloride and a metal chloride. In particular, the metal chloride may be aluminum chloride (AlCl3).
[0024] The aluminum chloride and sodium chloride are preferably mixed at a molar ratio of 3:2 to 1:1. The reason for using aluminum chloride and sodium chloride is that both are water soluble, making it relatively easy to remove the salt in subsequent steps.
[0025] That is, although the present invention will be described with reference to a mixture of aluminum chloride and sodium chloride, any water-soluble metal salt can be used. The pretreated pitch and salt are mixed at a mixing ratio of 5 to 30 wt % pitch and 70 to 95 wt % salt.
[0026] Next, as in step S30, the mixture of pitch and salt is ground and stirred. In this case, a ball mill can be used for the grinding and stirring, and the particle size of the mixture is homogenized and stirred to mix the pitch and salt uniformly.
[0027] Next, the ground mixture is heated and stirred at a temperature of 150 to 300°C for 30 to 180 minutes to pyrolyze and polymerize the pitch to produce mesophase pitch. The heating temperature is preferably 250°C. This is a condition for obtaining MCMB of the desired quality while keeping the heating temperature as low as possible.
[0028] At this time, the atmosphere for heating and stirring is maintained in a purged state by supplying an inert gas such as nitrogen, and heating is performed while stirring using a stirrer. The stirrer is a mechanical stirrer, and the stirring is performed at a relatively low speed of 80 to 120 RPM. The RPM of such a stirrer may vary depending on the viscosity and amount, and stirring can be performed in the range of 80 to 400 RPM.
[0029] This heating melts the aluminum chloride, which has a low melting point, and the pitch, which is uniformly dispersed in the melt, is heated uniformly throughout, thereby improving heating efficiency compared to a method in which powdered pitch is directly heated.
[0030] Therefore, the present invention can induce the reaction at a lower temperature than the conventional reaction temperature of pitch, thereby reducing the energy required for producing MCMB.
[0031] Next, as in step S50, the heated and stirred mixture is cooled and the salt is removed. The cooling is carried out in an atmosphere where nitrogen is supplied to prevent reaction with other foreign matter, and after the cooling is completed, the mixture is washed with distilled water to remove salts, thereby obtaining mesophase pitch.
[0032] As described above, the aluminum chloride and sodium chloride used in the present invention are both water-soluble metal salts and can be easily removed by washing with distilled water to obtain mesophase pitch.
[0033] The desalted mesophase pitch is then post-processed to obtain MCMB, as in step S60. In this case, the post-treatment is to dry the mesophase pitch using an oven, and after drying in a vacuum atmosphere at 40° C., the heat treatment reactants are removed from the dried mesophase pitch through solvent extraction to produce MCMB.
[0034] The solvent extraction can be carried out using known extraction methods such as extraction using heavy oil. It has been confirmed that the MCMB produced in this manner has excellent quality regardless of the quality of the raw pitch, which will be described in more detail through the following experimental examples.
[0035] Specifically, the present invention is characterized in that isotropic pitch is dispersed in a molten metal salt and heat-treated to obtain anisotropic mesophase pitch. In order to confirm the superiority of the MCMB manufacturing method according to the present invention, a small-scale experiment was carried out as described below, and the characteristics of the MCMB manufactured according to the present invention were confirmed by Raman spectroscopy, etc., thereby confirming the effects of the present invention.
[0036] <Experimental Example> FIG. 2 is a graph showing the results of Raman spectroscopy of an isotropic pitch having a softening point of 150. The present invention is characterized by providing a method for obtaining anisotropic mesophase pitch using an isotropic pitch having a softening point of 150 or 115 as a raw material. The Raman spectroscopy result graph of the anisotropic mesophase pitch to be obtained in the present invention is shown in FIG. 3.
[0037] The experiment was carried out multiple times under various conditions as shown in Table 1 below. For example, experiments were conducted on mixtures of AlCl3 and NaCl, and mixtures of KCl and ZnCl2, and the salt mixing ratios were varied in a variety of ways.
[0038] The feedstock pitches used in the experiment were anisotropic pitches represented as 1 and 2 in Table 1, and isotropic pitches represented as 3 and 4. The isotropic pitch represented as 3 is the softening point 150 pitch mentioned above, and 4 is the softening point 115 pitch.
[0039] In addition, the temperature and time conditions of the heat treatment were varied, and the stirring conditions using a stirrer during the heat treatment were also changed.
[0040] [Table 1]
[0041] As a result of the experiment, it was confirmed that when a mixture of KCl and ZnCl2 was used as a salt, it was impossible to use it because it was not easy to remove the salt from the mesophase pitch.
[0042] Thus, in the present invention, a water-soluble metal salt is used to provide the melt. Below, we describe the meaningful experimental results in the experiments in Table 1. <Experimental result 1> As a meaningful experimental result, in Experiment No. 3 in Table 1, a mixture of aluminum chloride and sodium chloride was used as the molten salt, pitch and salt were mixed in a weight ratio of 1:10, and heat-treated at 300°C for 180 minutes. Stirring was omitted.
[0043] Mesophase pitch was produced under these conditions, and the results were confirmed. The Raman analysis results are shown in Figure 4. Referring to Figure 4, it can be seen that the results of Experiment No. 3 are similar to the Raman shift results of Figure 3. That is, it was confirmed that anisotropic mesophase pitch can be produced using isotropic pitch.
[0044] It was also confirmed that processing for producing MCMBs is possible even at relatively low temperatures. However, even though the mixture was heated at 300°C, some vaporization of the pitch and molten salt mixture was observed.
[0045] <Experimental result 2> The results of experiment number 4 are shown in FIG. Experiment No. 4 is the result of lowering the heating temperature to 250° C. under the conditions of Experiment No. 3 described above, while keeping other factors the same.
[0046] Even when the temperature is lowered to 250° C., a result similar to the Raman shift result of FIG. 3 can be obtained, and the manufacturing cost can be further reduced by further lowering the heating temperature.
[0047] In particular, since no vaporization phenomenon occurred, a Raman shift graph closer to FIG. 3 than the result of Experiment No. 3 was observed. <Experimental result 3> The Raman shifts resulting from experiment number 17 are shown in FIG.
[0048] In experiment number 17, only the heating temperature was lowered to 200°C under the conditions of experiment number 3. The Raman shift results were similar to those shown in Figures 4 and 5, but it was confirmed that the peak intensity (Intensity au) was reduced.
[0049] Based on the above experimental results, the present invention has found that it is preferable to apply heating conditions of 150 to 300°C, and in particular, when heating at 250°C, results most similar to the targeted results were obtained.
[0050] The above experiment was conducted to confirm the heating temperature conditions, and to confirm the appropriate heating maintenance time, the characteristics were analyzed by changing the heating time under the same conditions as the above experiment, with the temperature fixed at 250°C.
[0051] <Experimental result 4> The basic experimental conditions were the same as in Experiment No. 4, but the heating time was shortened from 180 minutes to 120 minutes. The results are shown in FIG.
[0052] As shown in FIG. 7, even though the heating time was shortened to 120 min, the Raman results were very similar to the targeted results. <Experimental result 5> FIG. 8 shows the results of an experiment in which the heating time was further shortened to 60 minutes under the experimental conditions of Experiment No. 4.
[0053] The Raman shift pattern is the same as in Experiment 5, which was maintained for 120 minutes, but it can be seen that the intensity is lower. Through these various experiments, it was confirmed that a heating temperature in the range of 150 to 300°C and a heating time of 30 to 180 minutes can produce anisotropic mesophase pitch even when using low-quality isotropic pitch.
[0054] In order to obtain more diverse experimental results, the mixture ratio of isotropic pitch and salt was adjusted. <Experimental result 6> The experimental conditions for experiment number 4 were a mixture of aluminum chloride and sodium chloride, and the isotropic pitch and salt mixture were mixed in a weight ratio of 1:10. The experimental conditions for experiment number 5 were changed to 1:2.
[0055] The results of the experiment under the conditions of Experiment No. 5 are shown in FIG. As shown in the figure, it was possible to confirm that there was a large difference from the target Raman shift result.
[0056] This can be understood as being because the amount of molten salt in which the isotropic pitch is dispersed is small, and the isotropic pitch is not heated uniformly. <Experimental result 7> Different from experiment number 5, in experiment number 6, the mixing weight ratio of isotropic pitch and salt mixture was 1:20, and the ratio of salt was increased.
[0057] The experimental results are shown in FIG. The Raman shift shape was similar to the target result, but the peak intensity was slightly lower.
[0058] Based on these experimental results, it was confirmed that the appropriate ratio of isotropic pitch and salt mixture is 5-30 wt% pitch and 70-95 wt% salt. <Experimental result 8> Moreover, in order to evaluate the effect of stirring during heating, the experimental results of Experiment No. 11, in which stirring was performed using a stirrer under the same conditions as Experiment No. 4, are shown in FIG.
[0059] Referring to FIG. 11, compared with the result without stirring (see FIG. 7), it was possible to obtain a result that was closer to the target result. It has been demonstrated that stirring the molten salt under heating improves the uniformity of heat distribution, allowing the isotropic pitch to be heated more uniformly and exhibit better properties.
[0060] Finally, an experiment was carried out to confirm whether or not a mesophase pitch of excellent quality could be obtained when the present invention was applied to an isotropic pitch having a softening point of 115. <Experimental Result 9> In experiment number 19 in Table 1, 115 grade isotropic pitch was used, a mixture of aluminum chloride and sodium chloride was used as the molten salt, the weight ratio of the isotropic pitch to the molten salt was 1:10, the heating temperature was 250°C, and the mixture was heated for 180 minutes, with the molten salt being stirred during heating.
[0061] The results obtained in such an experiment are shown in FIG. As can be seen from FIG. 12, even when using 115 grade isotropic pitch, a mesophase pitch of excellent quality could be obtained.
[0062] Therefore, the present invention has the advantage that it is possible to produce MCMB of desired quality while using lower-cost raw material pitch, thereby minimizing production costs.
[0063] It will be obvious to those having ordinary skill in the art to which the present invention pertains that the present invention is not limited to the above-described embodiments, and that various modifications and variations can be made without departing from the technical gist of the present invention. [Industrial Applicability]
[0064] INDUSTRIAL APPLICABILITY The present invention relates to a method for switching an isotropic pitch to an anisotropic pitch using the laws of nature, thereby saving energy, and has industrial applicability.
Claims
1. a) pre-treating a feed pitch; b) mixing the pretreated pitch with salt; c) grinding and agitating the mixture of pitch and salt; d) heating and stirring the ground mixture at a temperature of 150 to 300° C. for 30 to 180 minutes to pyrolyze and polymerize the raw pitch to produce mesophase pitch; e) cooling the heated and stirred mixture and then removing the salt; f) post-treating the desalted mesophase pitch to produce MCMB.
2. 2. The method for producing MCMB according to claim 1, wherein the raw pitch is an isotropic pitch having a softening point of 150 or 115.
3. a) the step The dried raw pitch is sieved to homogenize it to a particle size of 106 μm or less.
3. The method for producing MCMB according to claim 1 or 2, further comprising drying the homogenized raw pitch in an oven.
4. The salt of step b) is 3. The method for producing MCMB according to claim 1, wherein the metal chloride is a water-soluble metal chloride.
5. The metal chloride is The method for producing MCMB according to claim 4, characterized in that aluminum chloride and sodium chloride are mixed in a molar ratio of 3:2 to 1:
1.
6. 5. The method for producing MCMB according to claim 4, wherein the mixing ratio of the raw pitch and the metal chloride is 5 to 30 wt % raw pitch and 70 to 95 wt % salt.
7. e) step comprises 5. The method for producing MCMB according to claim 4, wherein the water-soluble salts are removed by washing with distilled water.
8. f) step comprises After drying the mesophase pitch in a vacuum atmosphere, 2. The method for producing MCMB according to claim 1, wherein the MCMB is produced by solvent extraction.
Citation Information
Patent Citations
Method for preparing carbon microspheres with controllable particle size
CN105858640A
Tansosenigenryopitsuchino seizohoho
JP1976060281A
Production of carbon material
JP1990049095A